The use of implants in the occlusal rehabilitation of a partially edentulous patient: a clinical report - Yunus, N.; Abdullah, H.; Hanapiah, F. (Elsevier, 2001)
This article describes the occlusal rehabilitation of a partially edentulous patient who did not want a removable partial denture. Implants and extensive fixed restorations were used to restore posterior support and treat severely worn dentition, respectively. The treatment offered the patient a functional and esthetic result.